2016
DOI: 10.1007/s00233-016-9785-x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse semigroups associated with labelled spaces and their tight spectra

Abstract: The notion of a labelled space was introduced by Bates and Pask in generalizing certain classes of C*-algebras. Motivated by Exel's work on inverse semigroups and combinatorial C*-algebras, we associate each weakly left resolving labelled space with an inverse semigroup, and characterize the tight spectrum of the latter in a way that is reminiscent of the description of the boundary path space of a directed graph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 12 publications
0
45
0
Order By: Relevance
“…We say that a path µ is a prefix of a path ξ if ξ = µν for some path ν. 1 It is usual to use s instead of d and call it the source map, however we use Katsura's convention [7].…”
Section: The Boundary Path Space Of a Graphmentioning
confidence: 99%
“…We say that a path µ is a prefix of a path ξ if ξ = µν for some path ν. 1 It is usual to use s instead of d and call it the source map, however we use Katsura's convention [7].…”
Section: The Boundary Path Space Of a Graphmentioning
confidence: 99%
“…It is worth pointing out that in the case of a labelled space that is weakly left-resolving and normal, if a filter in a complete family is an ultrafilter, then all filters in the family coming before it are also ultrafilters [4,Proposition 5.7]. Theorem 4.13).…”
Section: Filters In E(s)mentioning
confidence: 99%
“…[4], Theorems 5.10 and 6.7). Let (E, L, B) be a weakly left-resolving, normal labelled space and S be its associated inverse semigroup.…”
mentioning
confidence: 96%
“…In [5], the authors applied Exel's construction [7] to an inverse semigroup defined from a labelled space with multiplication inspired by the relations defining the C*-algebra of the labelled space. The tight spectrum was characterized in Theorem 6.7 of [5]. In the particular case of a labelled space defined from a graph as in [2], the authors found [5,Proposition 6.9] that the tight spectrum is homeomorphic to the boundary path space of the underlying graph (studied by Webster in [12]).…”
Section: Introductionmentioning
confidence: 99%
“…The tight spectrum was characterized in Theorem 6.7 of [5]. In the particular case of a labelled space defined from a graph as in [2], the authors found [5,Proposition 6.9] that the tight spectrum is homeomorphic to the boundary path space of the underlying graph (studied by Webster in [12]).…”
Section: Introductionmentioning
confidence: 99%